Lead in agricultural soils and cultivated pastures irrigated with river water contaminated by mining activity - Orellana, E.P.; Custodio, M.; Bastos, C.; Cuadrado, W. (Wydawnictwo Naukowe Gabriel Borowski (WNGB), 2019)
Agricultural soils irrigated with contaminated water from metallurgical mining activities for more than 70 years constitute an environmental problem and a concern for food security and human health. The presence of lead in soil and cultivated pastures is highly dangerous, due to its toxicity, persistence and accumulation in plants and animals (cattle). This element enters the trophic chain of humans due to the intake of meat, milk and its derivatives. The concentration of lead determined in the soil and the cultivated pastures with Lolium x hybridum Hausskn and Medicago sativa L. Soil and pastures samples collected from plots irrigated with river water contaminated with heavy metals at a depth of 0-20 cm. The content of Pb determined by the atomic absorption spectrophotometry. The results showed lead concentrations in soil in the range of environmental quality standards for soils according to Peruvian regulations. In soil with L. x hybridum and M. sativa the average content of lead was 57.17 ± 6.29 mg.kg-1 and 57.19 ± 8.99 mg.kg-1; in aerial tissues were 1.17 ± 0.69 mg.kg-1 and 1.62 ± 0.68 mg.kg-1 respectively. In addition, no significant differences observed in the Pb content in soil and plant tissues. The bioconcentration factor (BCF) in the aerial tissues of L. x hybridum and M. sativa was less than one and they were not significant. Therefore, irrigation with long-term contaminated water is not a concern for farmers in the Mantaro Valley. Therefore, it concludes that the irrigation with long-term contaminated water is not a concern for farmers in the Mantaro Valley.